2019
DOI: 10.1101/601047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No evidence for disruption of global patterns of nest predation in shorebirds

Abstract: †These authors formed the core team behind the Technical Comment. The remaining authors are listed alphabetically according to their first name. Affiliations located after Acknowledgements.Abstract Kubelka et al. (Science, 9 November 2018, p. 680-683) claim that climate change has disrupted patterns of nest predation in shorebirds. They report that predation rates have increased since the 1950s, especially in the Arctic. We describe methodological problems with their analyses and argue that there is no solid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Given this broad pattern, it is plausible that trajectories of shorebird populations stopping over in the bay are governed by factors beyond conditions encountered in the Delaware Bay. For example, one hypothesis concerns Arctic climate change altering patterns of reproductive output but to date, no clear pattern linking shorebird declines to Arctic breeding conditions has emerged (Weiser et al, 2018; Bulla et al, 2019). Shorebird population declines instead have been linked to adult survival (Weiser et al, 2020), with conditions that reduce survival typically encountered away from breeding sites (Weiser et al, 2017) during migration, stopover and wintering periods (Murray et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this broad pattern, it is plausible that trajectories of shorebird populations stopping over in the bay are governed by factors beyond conditions encountered in the Delaware Bay. For example, one hypothesis concerns Arctic climate change altering patterns of reproductive output but to date, no clear pattern linking shorebird declines to Arctic breeding conditions has emerged (Weiser et al, 2018; Bulla et al, 2019). Shorebird population declines instead have been linked to adult survival (Weiser et al, 2020), with conditions that reduce survival typically encountered away from breeding sites (Weiser et al, 2017) during migration, stopover and wintering periods (Murray et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…More than half of North America's shorebird species are considered to be of high conservation concern due to unabated threats and population declines (U.S. Shorebird Conservation Partnership, 2014;Hope et al, 2019). Given this broad pattern, it is plausible that trajectories (Weiser et al, 2018;Bulla et al, 2019). Shorebird population declines instead have been linked to adult survival (Weiser et al, 2020), with conditions that reduce survival typically encountered away from breeding sites (Weiser et al, 2017) during migration, stopover and wintering periods (Murray et al, 2018).…”
Section: Water Temperaturementioning
confidence: 99%
“…Nor did we find any correlations between nesting data and year to year variability in our fox or lemming measures (but see below), which is similar to findings by Machín et al (2019) in sub-Arctic Sweden. Increased nest predation particularly in the Arctic has been postulated by Kubelka et al (2018) but questioned by Bulla et al (2019) while still maintained by Kubelka et al (2019) and refused by Bulla et al (2021). We have little to add to this discussion, since we are not able to distinguish between the effects of the apparent increased fox activity and the effects of our own activities at nests.…”
Section: Clutch Size and Reproductive Successmentioning
confidence: 90%
“…Kubelka et al (2018) suggested that increases in Arctic wader nest predation are consistent with climate-induced changes to traditional predator-prey relationships; in particular disrupted lemming cycles and the behaviour and distribution of nest predators. However, Bulla et al (2019) subsequently disputed that nest predation rates have been disrupted due to climate change. Nonetheless, the indirect impact of disrupted lemming population cycles on Arctic-breeding birds was discussed in several earlier articles.…”
Section: Altered Community Composition and Interspecific Interactionsmentioning
confidence: 99%